Etnografía colombiana : una visión a través de los años. Herramienta para la apropiación social del conocimiento. (2022)
The social appropriation of knowledge is a process that allows knowledge to be disseminated and allows populations to be interested, take advantage of and make that knowledge their own for their lives. It is a way to get out of the scientific bubble to strengthen the understanding of all people without the need for them to be experts on the proposed topic. In Colombia, endless anthropological documents have been created that hope to be useful to all people who wish to study them; however, due to the volume and dispersion of documents both on the Internet and in physical libraries, it is difficult to access them. That is why the objective of the research is to develop a digital tool that facilitates the social appropriation of knowledge about ethnographic and anthropological studies in Colombia.